Sistem Diagnosis Penyakit Tumbuhan Mangga Menggunakan Metode Naive Bayes - Mochammad Taufiqi Effendi; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mango productivity can compete with the rapid local and export markets which are opportunities for Indonesian farmers, but farmers must increase the yield of mangoes to increase marketing competitiveness due to the various inhibiting aspects including diseases. In the Mango Plant Diagnosis System Using the Naive Bayes Method aimed to assist farmers in overcoming the problem of diagnosing mango plant diseases. This system wad built based on the problems that occurred in farmers, namely the difficulty in recognizing the types of mango plants, due to the many similarities in the symptoms of mango plant diseases. Mangoes have long been felt by farmers causing the deflation of mangoes' crop yields. In 2015 a decrease of 10.39 percent from 2014 was 2.43 million tons to 2.17 million tons. Naive Bayes method which selected in this study was a method used to predict probability. This system was used on Android systems, because it was quite efficient and popular among the public. The results of testing this study indicate that, in testing the accuracy of 30 test data get an accuracy rate of 87.5%.